IMPLEMENTASI THE BEAR CARD FEELINGS DALAM BIMBINGAN KLASIKAL UNTUK MELATIH KEMAMPUAN BERBICARA SISWA - Ramdhiani, Ainun Nur Fitri (At-Taujih: Jurnal Bimbingan dan Konseling Islam, 2025)
This study aims to determine the implementation and effectiveness of the bear card feelings in classical guidance services to help train students' speaking skills at MTsN 1 Banyumas, precisely in class VIIC. The method used in this study is descriptive qualitative where data is obtained from the results of interviews and observations conducted by researchers related to student behavior and responses after being given services. The sampling technique used is purposive sampling with two criteria, namely 1) students have participated in classical guidance services with the bear card feelings media, and 2) are willing to be participants in interviews and observations submitted by researchers. Data was obtained through interviews and observations of students as well as documentation during the service process. Data analysis techniques used include data reduction, data presentation and drawing conclusions. Data reduction is done by selecting and also conveying important data presented in the form of descriptive narratives that describe the response and also the service process taking place. The results of this study indicate that classical guidance services implemented with the simulation game method using the bear card feelings tool can help students practice their public speaking skills. Thus, it is necessary to develop more innovative and fun methods, so that students have a deep understanding of the material presented in a fun way